FAO Agricultural services bulletin; No.125 - Andrew W Shepherd (FAO, 1997)
This book discusses the theoretical benefits of such service and evaluates experiences with MIS around the world. It includes the need to rsearch the way the marketing system functions and the identification of appropriate institutional arrangements for operation of the service, as well as collection, analysis and dessimination of the data and the choice of products and the markets to be covered